Additive for recovering thermosetting material, recoverable thermosetting composition and application thereof

By using additives of copolymers and processing additives in thermoset materials, the recyclable decomposition products are generated, which solves the problem of recycling thermoset materials and achieves an efficient and environmentally friendly recycling and reuse process.

CN119855872APending Publication Date: 2025-04-18JUPITER SANGYO CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380060032.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-13
Filing Date
2023-09-12
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently recycle and reuse thermoset materials, and traditional incineration methods have problems with low energy utilization and air pollution.

Method used

An additive containing a copolymer and processing aid is employed that reacts with a thermosetting material to produce a recyclable decomposition product, and a recovery procedure is simplified by heating and separation processes to generate a new resin material.

Benefits of technology

It realizes efficient recycling and reuse of thermoset materials, reduces energy consumption and pollution emissions, and complies with the principles of green chemistry and circular economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005272650930000071
    Figure BDA0005272650930000071
  • Figure BDA0005272650930000081
    Figure BDA0005272650930000081
  • Figure BDA0005272650930000082
    Figure BDA0005272650930000082
Patent Text Reader

Abstract

The invention discloses an additive for recovering thermoset materials, a recoverable thermoset composition and application thereof. Specifically, the composition of the additive comprises at least one copolymer having at least one carbamate group, at least one carbonate group and / or at least one urea group, and the number average molecular weight of the copolymer ranges from 100 to 50,000 Da.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. patent application No. 63 / 405,939 filed with the U.S. Patent Office on September 13, 2022, with invention name “An additive for recycling thermosetting materials, a recyclable thermosetting composition and its application”, the entire contents of which are incorporated by reference into this application. Technical Field

[0003] The invention discloses an additive for recycling thermosetting materials, a recyclable thermosetting composition and its application. Specifically, the additive comprises a copolymer and a processing aid. Background Art

[0004] Thermosets are polymers with high molecular weight that can replace other materials such as thermoplastics, metals, wood, etc. due to their structural and physical properties, cost and processability.

[0005] In the field of known technology, thermosetting materials are difficult to recycle and reuse due to their cross-linked three-dimensional chemical structure. Therefore, methods for recycling thermosetting materials are usually very expensive and inefficient. Traditionally, waste thermosetting materials are treated by incineration, which has the disadvantages of low energy utilization and air pollution. Mechanical recycling methods can only recycle a small amount of inorganic fillers. So far, the recycling of waste thermosetting materials still has environmental and cost barriers that are difficult to break through.

[0006] In summary, in the technical field of thermosetting materials, there is still an urgent need for research and development of technical solutions for providing recyclable thermosetting materials that comply with green chemistry and circular economy in order to break through current technical bottlenecks and meet future industry needs. Summary of the invention

[0007] According to the above invention background, in order to meet the needs of the industry, the first purpose of the present invention is to provide an additive for recycling thermosetting materials to solve the problems of difficulty in recycling and reuse, complicated recycling procedures, and difficulty in recycling. The additive or polymer of the present invention reacts with thermosetting materials to obtain recyclable decomposition products; the decomposition products can be recycled to manufacture new thermosetting materials; the decomposition products, waste thermosetting materials and the above additives can be mixed to simplify the recycling procedures and regenerate new resin materials. Accordingly, the present invention provides a solution for recycling and reuse of thermosetting materials that conforms to the principles of green chemistry and is technologically innovative.

[0008] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.

[0009] The first object of the present invention is to disclose an additive composition for recycling thermosetting materials comprising at least one copolymer and / or at least one processing aid.

[0010] Specifically, the copolymer has at least one urethane group, at least one carbonate group and / or at least one urea group, and the number average molecular weight of the copolymer ranges from 100 to 50,000 Da.

[0011] Specifically, the processing aid comprises amines, catalysts, solvents or mixtures thereof. Preferably, the processing aid is a hydroxyl compound, an amino compound, an amino-hydroxy compound or a combination thereof.

[0012] Specifically, the catalyst comprises amines, imidazoles, metals and their salts, Lewis acids or Lewis bases. The amines comprise quaternary ammonium salts, dimethylamine, diethylamine, triethylamine, triethanolamine, dimethylaniline or pyridine. The amidine catalyst comprises 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,4-diazabicyclo[2.2.2]octane (DBACO) or aromatic dimethylamine compounds. The aliphatic amine comprises diethylenetriamine (DETA), triethylenetetramine (TETA) or polyether polyamines. The imidazole catalyst comprises imidazolidinyl urea, diethyltetramethylimidazole or a mixture thereof. The metal and its salts comprise aluminum, cobalt, nickel, copper, iron, zinc, chromium, vanadium, titanium, manganese, potassium, zirconium and oxides, halides, sulfates, nitrates or phosphates thereof. The Lewis acid comprises boron trifluoride and its complexes. The Lewis base includes a C1-C10 straight-chain or branched alkyl phosphorus compound, an aromatic phosphorus compound or a halogen-substituted phosphorus compound. Other types of catalysts include thiourea and its derivatives, titanate or a rare earth metal compound.

[0013] Specifically, based on the weight of the thermosetting material, the added amount of the catalyst is 1.5-15 wt.%.

[0014] Specifically, the solvent comprises an aprotic solvent or an ionic liquid. The aprotic solvent comprises dimethylformamide (DMF), dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO) or N-methyl-2-pyrrolidone (NMP). The ionic liquid is a pyridinium cationic ionic liquid or an imidazolium cationic ionic liquid and its corresponding anion, and the anion is selected from the following groups: BF4-, B(CN)4-, CH3BF3-, CH2CHBF3-, CF3BF3-, C2F5BF3-, n-C3F7BF3-, n-C4F9BF3-, PF6-, CF3CO2-, CF3SO3-, N(SO2CF3)2-, N(COCF3)(SO2CF3)-, N(SO2F)2-, N(CN)2-, C(CN)3-, SCN-, SeCN-, CuCl2-, AlCl4- and F(HF)2.3-.

[0015] Specifically, the processing aid can assist the copolymer of the present invention and the thermosetting material to form a uniform phase. At the same time, the processing aid also has the technical effect of catalyzing the reaction between the copolymer of the present invention and the thermosetting material. Generally, hydroxy compounds, amino compounds, hydroxy-amino compounds or their combinations react with thermosetting materials to obtain intermediate products with small molecular weights, and the intermediate products have better compatibility with the copolymer of the present invention, such as (urethane-carbonate) copolymers or / and copolymers with carbonate groups.

[0016] Specifically, the additive comprises 0.5-99.5 wt. % of a copolymer and 99.5-0.5 wt. % of a processing aid.

[0017] The second object of the present invention is to disclose a recyclable thermosetting composition, which comprises an additive (or copolymer) and a thermosetting material, wherein the total weight percentage of the additive (or copolymer) and the weight percentage of the thermosetting material is 100%.

[0018] Specifically, the copolymer has at least one carbamate group, at least one carbonate group and / or at least one urea group, and the weight percentage of the copolymer is 0.1-85wt.%, based on the total weight of the recyclable thermosetting composition. The thermosetting material comprises polyurethane, polyurethane foam material, epoxy resin, phenolic resin, reinforced composite material, benzoxazine resin, acrylic resin or a combination thereof.

[0019] Specifically, the additive (or copolymer) and the thermosetting material are mixed or blended to obtain the recyclable thermosetting composition. The recyclable thermosetting composition is a mixture of a homogeneous phase or a heterogeneous phase.

[0020] Specifically, the additive (or copolymer) and the thermosetting material can generate a decomposition product of the thermosetting material at a high temperature, and the decomposition product of the recyclable thermosetting material can be recycled and regenerated to manufacture new thermosetting material.

[0021] The third object of the present invention is to provide a process for recycling waste thermosetting materials, which includes but is not limited to the following steps.

[0022] Step 1: providing a mixture, the mixture comprising at least one copolymer, at least one processing aid and at least one waste thermosetting material, the copolymer having at least one urethane group, at least one carbonate group and / or at least one urea group, and the weight percentage of the copolymer based on the total weight of the mixture is 0.1-85wt.%.

[0023] Step 2: heating the mixture to 50-220° C. to obtain a product, which contains inorganic and organic substances.

[0024] Step 3: Execute a first procedure to separate the inorganic and organic substances, wherein the first procedure comprises extraction, crystallization, distillation, filtration or a combination thereof; the organic substances comprise organic compounds with higher molecular weight and organic compounds with lower molecular weight.

[0025] Step 4: Perform a second procedure to separate the organic compound with a higher molecular weight and the organic compound with a lower molecular weight, wherein the second procedure comprises extraction, crystallization, distillation, filtration or a combination thereof, wherein the organic compound with a higher molecular weight is a raw material for recycling epoxy resin, polyurethane, benzoxazine resin, phenolic resin, acrylic resin, polyurethane foam material or reinforced composite material.

[0026] Specifically, the copolymer has at least one urethane group, at least one carbonate group and / or at least one urea group, and the number average molecular weight of the copolymer ranges from 100 to 50,000 Da.

[0027] Specifically, the processing aid is a decomposer and further comprises at least one catalyst and at least one solvent.

[0028] Specifically, the catalyst comprises amines, imidazoles, metals and their salts, Lewis acids or Lewis bases. The amines comprise quaternary ammonium salts, dimethylamine, diethylamine, triethylamine, triethanolamine, dimethylaniline or pyridine. The amidine catalyst comprises 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,4-diazabicyclo[2.2.2]octane (DBACO) or aromatic dimethylamine compounds. The aliphatic amine comprises diethylenetriamine (DETA), triethylenetetramine (TETA) or polyether polyamines. The imidazole catalyst comprises imidazolidinyl urea, diethyltetramethylimidazole or a mixture thereof. The metal and its salts comprise aluminum, cobalt, nickel, copper, iron, zinc, chromium, vanadium, titanium, manganese, potassium, zirconium and oxides, halides, sulfates, nitrates or phosphates thereof. The Lewis acid comprises boron trifluoride and its complexes. The Lewis base includes a C1-C10 straight-chain or branched alkyl phosphorus compound, an aromatic phosphorus compound or a halogen-substituted phosphorus compound. Other types of catalysts include thiourea and its derivatives, titanate or a rare earth metal compound.

[0029] Specifically, based on the weight of the thermosetting material, the added amount of the catalyst is 1.5-15 wt.%.

[0030] Specifically, the solvent comprises an aprotic solvent or an ionic liquid. The aprotic solvent comprises dimethylformamide (DMF), dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO) or N-methyl-2-pyrrolidone (NMP). The ionic liquid is a pyridinium cationic ionic liquid or an imidazolium cationic ionic liquid and its corresponding anion, and the anion is selected from the following groups: BF4-, B(CN)4-, CH3BF3-, CH2CHBF3-, CF3BF3-, C2F5BF3-, n-C3F7BF3-, n-C4F9BF3-, PF6-, CF3CO2-, CF3SO3-, N(SO2CF3)2-, N(COCF3)(SO2CF3)-, N(SO2F)2-, N(CN)2-, C(CN)3-, SCN-, SeCN-, CuCl2-, AlCl4- and F(HF)2.3-.

[0031] Specifically, the inorganic material includes glass fiber, inorganic matrix or inorganic fillers of different types.

[0032] Specifically, the organic matter includes relatively high molecular weight organic compounds and relatively low molecular weight organic compounds.

[0033] Specifically, the relatively high molecular weight organic compound is a raw material for recycling epoxy resin, polyurethane, phenolic resin, acrylic resin, benzoxazine resin, polyurethane foam material or reinforced composite material.

[0034] Specifically, the relatively low molecular weight organic compound comprises urea, polyurea, cyclic urea, cyclic urethane monomers or oligomers.

[0035] In summary, the present invention provides a novel additive for recycling thermosetting materials. The composition of the additive includes a copolymer having at least one carbamate group, at least one carbonate group, and / or at least one urea group. The technical effects of the present invention include but are not limited to the following: the additive or polymer reacts with the thermosetting material to obtain a decomposition product that can be recycled and reused; the decomposition product can be recycled to manufacture a new thermosetting material; the decomposition product is mixed with the waste thermosetting material and the above-mentioned additive to simplify the recycling procedure and regenerate a new resin material. Accordingly, the present invention provides a solution for recycling and reusing thermosetting materials that conforms to the principles of green chemistry and is technologically innovative.

[0036] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above-mentioned structure and other purposes, features and advantages of the present invention more obvious and easy to understand, some specific embodiments are listed below, and the detailed description is as follows in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a copolymer of PCC-0.25 1 H-NMR spectrum.

[0038] Figure 2 It is a copolymer of PCC-0.5 1 H-NMR spectrum.

[0039] Figure 3 It is a copolymer of PCC-0.99 1 H-NMR spectrum.

[0040] Figure 4 It is a copolymer of PCC-1.0S 1 H-NMR spectrum.

[0041] Figure 5 is the FTIR spectrum of sample PCC-E1.

[0042] Figure 6 This is the FTIR spectrum of sample PCC-E1-M1.

[0043] Figure 7 This is the FTIR spectrum of sample rEP-1.

[0044] Figure 8 This is the FTIR spectrum of sample PCC-PF1.

[0045] Fig. 9 This is the FTIR spectrum of sample PCC-PF1-M1.

[0046] Fig.10 This is the FTIR spectrum of sample rPF-1FTIR.

[0047] Fig.11 This is the FTIR spectrum of sample PCC-PMMA1.

[0048] Fig.12 This is the FTIR spectrum of sample PCC-PMMA1-M1.

[0049] Fig.13 It is the FTIR spectrum of sample rPMMA-1.

[0050] Fig.14 is the FTIR spectrum of sample PCC-PU1.

[0051] Fig.15 This is the FTIR spectrum of sample PCC-PU-T1.

[0052] Fig.16 It is the FTIR spectrum of sample rPU-1.

[0053] Fig.17 This is the FTIR spectrum of sample PCC-BZ1.

[0054] Fig.18 This is the FTIR spectrum of sample PCC-BZ1-T1.

[0055] Fig.19 This is the FTIR spectrum of sample rBZ-1.

[0056] Fig. 20 is the FTIR spectrum of sample PCC-C1.

[0057] Fig.21 This is the FTIR spectrum of sample PCC-C1-R1.

[0058] Fig. 22 This is the FTIR spectrum of sample rC-1. DETAILED DESCRIPTION

[0059] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the specific implementation methods, structures, features and effects proposed according to the present invention are described in detail below in conjunction with the accompanying drawings and some specific embodiments.

[0060] A first embodiment of the present invention discloses an additive for recycling thermosetting materials.

[0061] Specifically, the composition of the additive for recycling thermosetting materials comprises at least one copolymer. Preferably, the composition of the additive for recycling thermosetting materials further comprises at least one processing aid.

[0062] Specifically, the copolymer has at least one urethane group, at least one carbonate group and / or at least one urea group, and the number average molecular weight of the copolymer ranges from 100 to 50,000 Da.

[0063] Specifically, the processing aid comprises amines, catalysts, solvents or mixtures thereof. Preferably, the processing aid is a hydroxyl compound, an amino compound, an aminohydroxyl compound or a combination thereof.

[0064] In a specific embodiment, the catalyst comprises amines, imidazoles, metals and their salts, Lewis acids or Lewis bases. The amines comprise quaternary ammonium salts, dimethylamine, diethylamine, triethylamine, triethanolamine, dimethylaniline or pyridine. The amidine catalyst comprises 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,4-diazabicyclo[2.2.2]octane (DBACO) or aromatic dimethylamine compounds. The aliphatic amine comprises diethylenetriamine (DETA), triethylenetetramine (TETA) or polyether polyamine. The imidazole catalyst comprises imidazolidinyl urea, diethyltetramethylimidazole or a mixture thereof. The metals and their salts comprise aluminum, cobalt, nickel, copper, iron, zinc, chromium, vanadium, titanium, manganese, potassium, zirconium and oxides, halides, sulfates, nitrates or phosphates thereof. The Lewis acid comprises boron trifluoride and its complexes. The Lewis base includes a C1-C10 straight-chain or branched alkyl phosphorus compound, an aromatic phosphorus compound or a halogen-substituted phosphorus compound. Other types of catalysts include thiourea and its derivatives, titanate or a rare earth metal compound.

[0065] In a specific embodiment, the catalyst is added in an amount of 1.5-15 wt. % based on the weight of the thermosetting material.

[0066] In one embodiment, the solvent comprises an aprotic solvent or an ionic liquid. The aprotic solvent comprises dimethylformamide (DMF), dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO) or N-methyl-2-pyrrolidone (NMP). The ionic liquid is a pyridinium cationic ionic liquid or an imidazolium cationic ionic liquid and its corresponding anion, and the anion is selected from the following groups: BF4-, B(CN)4-, CH3BF3-, CH2CHBF3-, CF3BF3-, C2F5BF3-, n-C3F7BF3-, n-C4F9BF3-, PF6-, CF3CO2-, CF3SO3-, N(SO2CF3)2-, N(COCF3)(SO2CF3)-, N(SO2F)2-, N(CN)2-, C(CN)3-, SCN-, SeCN-, CuCl2-, AlCl4- and F(HF)2.3-.

[0067] Specifically, the processing aid can assist the copolymer of the present invention and the thermosetting material to form a uniform phase. At the same time, the processing aid also has the technical effect of catalyzing the reaction between the copolymer of the present invention and the thermosetting material. Generally, hydroxy compounds, amino compounds, hydroxy-amino compounds or their combinations react with thermosetting materials to obtain intermediate products with small molecular weights, and the intermediate products have better compatibility with the copolymer of the present invention, such as (urethane-carbonate) copolymers or / and copolymers with carbonate groups.

[0068] In one embodiment, the additive comprises 0.5-99.5 wt % of the copolymer and 99.5-0.5 wt % of the processing aid. Preferably, the additive comprises 5-50 wt % of the copolymer and 95-50 wt % of the processing aid.

[0069] In one embodiment, the copolymer has at least one urethane group, at least one carbonate group and / or at least one urea group, and the number average molecular weight of the copolymer is in the range of 100-50,000 Da.

[0070] In one embodiment, the copolymer is a (urethane-carbonate) copolymer, a (urethane-urea) copolymer, a (carbonate-urea) copolymer, a (urethane-carbonate-urea) copolymer, or a combination thereof.

[0071] In one embodiment, the carbamate group has a structure as shown in Formula (1) or Formula (2).

[0072] Formula (1):

[0073]

[0074] Formula (2):

[0075] In a specific embodiment, R1 is a linear or branched alkyl group with 2-20 carbon atoms, a cyclic alkyl group with 3-8 carbon atoms, a polyether group with a molecular weight of 50-10,000, or a polysiloxane group with a molecular weight of 50-10,000; R2 is a linear or branched alkyl group with 2-20 carbon atoms, a cyclic alkyl group with 3-8 carbon atoms, a phenyl group, or an alkylphenyl group with 7-20 carbon atoms. or an alkylphenol group having 6 to 20 carbon atoms; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group or an amide group; X is a straight chain or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a polyether group having a molecular weight of 50 to 10,000 or a polysiloxane group having a molecular weight of 50 to 10,000 and n is an integer of 1 to 10.

[0076] In one embodiment, the carbonate group has a structure as shown in formula (3).

[0077] Formula (3):

[0078]

[0079] In one embodiment, R2 is a linear or branched alkyl group having 2-20 carbon atoms, a cyclic alkyl group having 3-8 carbon atoms, a phenyl group, an alkylphenyl group having 7-20 carbon atoms, or an alkylphenol group having 6-20 carbon atoms.

[0080] In one embodiment, the urea group has a structure as shown in formula (4).

[0081] Formula (4):

[0082]

[0083] In a specific embodiment, R1 is a straight chain or branched alkyl group with a carbon number of 2-20, a cyclic alkyl group with a carbon number of 3-8, a polyether group with a molecular weight of 50-10,000, or a polysiloxane group with a molecular weight of 50-10,000; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group, or an amide group; X is a straight chain or branched alkyl group with a carbon number of 2-20, a cyclic alkyl group with a carbon number of 3-8, a polyether group with a molecular weight of 50-10,000, or a polysiloxane group with a molecular weight of 50-10,000; and n is an integer of 1-10.

[0084] In a representative embodiment, the copolymer is a (urethane-carbonate) copolymer and has a structure as shown in formula (5).

[0085] Formula (5):

[0086]

[0087] In a specific embodiment, m in formula (5) is an integer selected from 1-100, and x and y are integers selected from 1-1000 respectively.

[0088] In one embodiment, the weight average molecular weight of the (urethane-carbonate) copolymer represented by formula (5) is in the range of 1,000-100,000 Da.

[0089] In one embodiment, the glass transition temperature (T g ) is greater than 50°C. In a preferred embodiment, the glass transition temperature (T g ) is greater than 80℃.

[0090] In one embodiment, the processing aid comprises diphenyl carbonate, ethanolamine, bisphenol A, anisole, polytetramethylene ether glycol or a combination thereof.

[0091] In one embodiment, the amino compound includes a primary amine, a diamine, a polyamine or a polyether diamine.

[0092] In one embodiment, the catalyst comprises a metal catalyst or an organic salt.

[0093] A second embodiment of the present invention discloses a recyclable thermosetting composition.

[0094] Specifically, the recyclable thermosetting composition comprises a copolymer and at least one thermosetting material, and the total weight percentage of the copolymer and the weight percentage of the thermosetting material is 100%.

[0095] Specifically, the copolymer has at least one carbamate group, at least one carbonate group and / or at least one urea group, and the weight percentage of the copolymer is 0.1-85 wt.% based on the total weight of the recyclable thermosetting composition.

[0096] Specifically, the copolymer and the thermosetting material are mixed or blended to form the above-mentioned recyclable thermosetting composition.

[0097] Specifically, the copolymer and the thermosetting material can generate a decomposition product of the thermosetting material at a high temperature, and the decomposition product of the recyclable thermosetting material can be recycled and regenerated to manufacture new thermosetting material.

[0098] The decomposition products of the recyclable thermosetting material include inorganic substances, relatively high molecular weight organic compounds and relatively low molecular weight organic compounds.

[0099] The relatively high molecular weight organic compound is a raw material for recycling epoxy resin, polyurethane, benzoxazine resin, phenolic resin, acrylic resin, polyurethane foam material or reinforced composite material.

[0100] The relatively low molecular weight organic compound comprises urea, polyurea, cyclic urea, cyclic amine ester monomer or oligomer.

[0101] In one embodiment, the recyclable thermosetting composition comprises recyclable polyurethane, recyclable polyurethane foam, recyclable epoxy resin, recyclable phenolic resin, recyclable composite material, recyclable benzoxazine resin, recyclable acrylic resin or a combination thereof.

[0102] In one embodiment, the recyclable polyurethane comprises 20-40 wt. % of the additive of the present invention or the copolymer described above.

[0103] In one embodiment, the recyclable epoxy resin comprises 30-60 wt. % of the additive of the present invention or the copolymer described above.

[0104] In one embodiment, the recyclable phenolic resin comprises 50-70 wt. % of the additive of the present invention or the copolymer described above.

[0105] In one embodiment, the recyclable benzoxazine resin comprises 10-25 wt. % of the additive of the present invention or the copolymer described above.

[0106] In one embodiment, the recyclable composite material comprises 35-85 wt. % of the additive of the present invention or the copolymer described above.

[0107] In one embodiment, the recyclable acrylic resin comprises 30-60 wt. % of the additive of the present invention or the copolymer described above.

[0108] In one embodiment, the copolymer is a (urethane-carbonate) copolymer, a (urethane-urea) copolymer, a (carbonate-urea) copolymer, a (urethane-carbonate-urea) copolymer, or a combination thereof.

[0109] In one embodiment, the number average molecular weight of the copolymer is in the range of 100-50,000 Da.

[0110] In one embodiment, the thermosetting material includes polyurethane, polyurethane foam material, epoxy resin, phenolic resin, reinforced composite material, benzoxazine resin, acrylic resin or a combination thereof.

[0111] In one embodiment, the carbamate group has a structure as shown in Formula (1) or Formula (2).

[0112] Formula (1):

[0113]

[0114] Formula (2):

[0115] In a specific embodiment, R1 is a linear or branched alkyl group with 2-20 carbon atoms, a cyclic alkyl group with 3-8 carbon atoms, a polyether group with a molecular weight of 50-10,000, or a polysiloxane group with a molecular weight of 50-10,000; R2 is a linear or branched alkyl group with 2-20 carbon atoms, a cyclic alkyl group with 3-8 carbon atoms, a phenyl group, an alkylphenyl group with 7-20 carbon atoms, or an alkylphenol group with 6-20 carbon atoms; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group, or an amide group; X is a linear or branched alkyl group with 2-20 carbon atoms, a cyclic alkyl group with 3-8 carbon atoms, a molecular weight of

[0116]

[0117] 50-10,000 polyether group or 50-10,000 polysiloxane group and n is an integer of 1-10.

[0118] In one embodiment, the carbonate group has a structure as shown in formula (3).

[0119] Formula (3):

[0120]

[0121] In a specific embodiment, R2 is a linear or branched alkyl group having 2-20 carbon atoms, a cyclic alkyl group having 3-8 carbon atoms, a phenyl group, an alkylphenyl group having 7-20 carbon atoms, or an alkylphenol group having 6-20 carbon atoms.

[0122] In one embodiment, the urea group has a structure as shown in formula (4).

[0123] Formula (4):

[0124]

[0125] In a specific embodiment, R1 is a straight chain or branched alkyl group with a carbon number of 2-20, a cyclic alkyl group with a carbon number of 3-8, a polyether group with a molecular weight of 50-10,000, or a polysiloxane group with a molecular weight of 50-10,000; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group, or an amide group; X is a straight chain or branched alkyl group with a carbon number of 2-20, a cyclic alkyl group with a carbon number of 3-8, a polyether group with a molecular weight of 50-10,000, or a polysiloxane group with a molecular weight of 50-10,000; and n is an integer of 1-10.

[0126] In another embodiment, the recyclable thermosetting composition further comprises 1.5-15 wt % of a processing aid, based on the total weight of the recyclable thermosetting composition.

[0127] In one embodiment, the processing aid comprises amines, catalysts, solvents or mixtures thereof. Preferably, the processing aid is a hydroxyl compound, an amino compound, an aminohydroxyl compound or a combination thereof.

[0128] In a specific embodiment, the catalyst comprises amines, imidazoles, metals and their salts, Lewis acids or Lewis bases. The amines comprise quaternary ammonium salts, dimethylamine, diethylamine, triethylamine, triethanolamine, dimethylaniline or pyridine. The amidine catalyst comprises 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,4-diazabicyclo[2.2.2]octane (DBACO) or aromatic dimethylamine compounds. The aliphatic amine comprises diethylenetriamine (DETA), triethylenetetramine (TETA) or polyether polyamine. The imidazole catalyst comprises imidazolidinyl urea, diethyltetramethylimidazole or a mixture thereof. The metals and their salts comprise aluminum, cobalt, nickel, copper, iron, zinc, chromium, vanadium, titanium, manganese, potassium, zirconium and oxides, halides, sulfates, nitrates or phosphates thereof. The Lewis acid comprises boron trifluoride and its complexes. The Lewis base includes a C1-C10 straight-chain or branched alkyl phosphorus compound, an aromatic phosphorus compound or a halogen-substituted phosphorus compound. Other types of catalysts include thiourea and its derivatives, titanate or a rare earth metal compound.

[0129] In a specific embodiment, the catalyst is added in an amount of 1.5-15 wt. % based on the weight of the thermosetting material.

[0130] In one embodiment, the solvent comprises an aprotic solvent or an ionic liquid. The aprotic solvent comprises dimethylformamide (DMF), dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO) or N-methyl-2-pyrrolidone (NMP). The ionic liquid is a pyridinium cationic ionic liquid or an imidazolium cationic ionic liquid and its corresponding anion, and the anion is selected from the following groups: BF4-, B(CN)4-, CH3BF3-, CH2CHBF3-, CF3BF3-, C2F5BF3-, n-C3F7BF3-, n-C4F9BF3-, PF6-, CF3CO2-, CF3SO3-, N(SO2CF3)2-, N(COCF3)(SO2CF3)-, N(SO2F)2-, N(CN)2-, C(CN)3-, SCN-, SeCN-, CuCl2-, AlCl4- and F(HF)2.3-.

[0131] A third embodiment of the present invention provides a waste thermosetting material recycling process, which includes the following steps.

[0132] Step 1: providing a mixture, the mixture comprising at least one copolymer, at least one processing aid and at least one waste thermosetting material, the copolymer having at least one urethane group, at least one carbonate group and / or at least one urea group, and the weight percentage of the copolymer based on the total weight of the mixture is 0.1-85wt.%.

[0133] Step 2: heating the mixture to 50-220° C. to obtain a product, which contains inorganic and organic substances.

[0134] Step 3: Execute a first procedure to separate the inorganic and organic substances, wherein the first procedure comprises extraction, crystallization, distillation, filtration or a combination thereof; the organic substances comprise organic compounds with higher molecular weight and organic compounds with lower molecular weight.

[0135] Step 4: Perform a second process to separate the organic compound with a higher molecular weight and the organic compound with a lower molecular weight, wherein the second process comprises extraction, crystallization, distillation, filtration or a combination thereof. The organic compound with a higher molecular weight is a raw material for recycling epoxy resin, polyurethane, benzoxazine resin, phenolic resin, acrylic resin, polyurethane foam material or reinforced composite material.

[0136] In one embodiment, the copolymer is a (urethane-carbonate) copolymer, a (urethane-urea) copolymer, a (carbonate-urea) copolymer, a (urethane-carbonate-urea) copolymer, or a combination thereof.

[0137] In one embodiment, the number average molecular weight of the copolymer is in the range of 100-50,000 Da.

[0138] In one embodiment, the thermosetting material includes polyurethane, polyurethane foam material, epoxy resin, phenolic resin, reinforced composite material, benzoxazine resin, acrylic resin or a combination thereof.

[0139] In one embodiment, the carbamate group has a structure as shown in Formula (1) or Formula (2).

[0140] Formula (1):

[0141]

[0142] Formula (2):

[0143] In a specific embodiment, R1 is a linear or branched alkyl group with 2-20 carbon atoms, a cyclic alkyl group with 3-8 carbon atoms, a polyether group with a molecular weight of 50-10,000, or a polysiloxane group with a molecular weight of 50-10,000; R2 is a linear or branched alkyl group with 2-20 carbon atoms, a cyclic alkyl group with 3-8 carbon atoms, a phenyl group, an alkylphenyl group with 7-20 carbon atoms, or an alkylphenol group with 6-20 carbon atoms; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group, or an amide group; X is a linear or branched alkyl group with 2-20 carbon atoms, a cyclic alkyl group with 3-8 carbon atoms, a molecular weight of

[0144]

[0145] A polyether group with a molecular weight of 50-10,000 or a polysiloxane group with a molecular weight of 50-10,000 and n is an integer of 1-10

[0146] In one embodiment, the carbonate group has a structure as shown in formula (3).

[0147] Formula (3):

[0148]

[0149] In a specific embodiment, R2 is a linear or branched alkyl group having 2-20 carbon atoms, a cyclic alkyl group having 3-8 carbon atoms, a phenyl group, an alkylphenyl group having 7-20 carbon atoms, or an alkylphenol group having 6-20 carbon atoms.

[0150] In one embodiment, the urea group has a structure as shown in formula (4).

[0151] Formula (4):

[0152]

[0153] In a specific embodiment, R1 is a straight chain or branched alkyl group with a carbon number of 2-20, a cyclic alkyl group with a carbon number of 3-8, a polyether group with a molecular weight of 50-10,000, or a polysiloxane group with a molecular weight of 50-10,000; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group, or an amide group; X is a straight chain or branched alkyl group with a carbon number of 2-20, a cyclic alkyl group with a carbon number of 3-8, a polyether group with a molecular weight of 50-10,000, or a polysiloxane group with a molecular weight of 50-10,000; and n is an integer of 1-10.

[0154] In one embodiment, the processing aid comprises amines, catalysts, solvents or mixtures thereof. Preferably, the processing aid is a hydroxyl compound, an amino compound, an aminohydroxyl compound or a combination thereof.

[0155] In a specific embodiment, the catalyst comprises amines, imidazoles, metals and their salts, Lewis acids or Lewis bases. Amines include quaternary ammonium salts, dimethylamine, diethylamine, triethylamine, triethanolamine, dimethylaniline or pyridine. Amidine catalysts include 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,4-diazabicyclo[2.2.2]octane (DBACO) or aromatic dimethylamine compounds. Aliphatic amines include diethylenetriamine (DETA), triethylenetetramine (TETA) or polyether polyamines. Imidazole catalysts include imidazolidinyl urea, diethyltetramethylimidazole or a mixture thereof. Metals and their salts include aluminum, cobalt, nickel, copper, iron, zinc, chromium, vanadium, titanium, manganese, potassium, zirconium and oxides, halides, sulfates, nitrates or phosphates thereof. Lewis acids include boron trifluoride and its complexes. Lewis bases include C1-C10 straight-chain or branched alkyl phosphorus compounds, aromatic phosphorus compounds or halogen-substituted phosphorus compounds. Other types of catalysts include thiourea and its derivatives, titanates or rare earth metal compounds.

[0156] In a specific embodiment, the catalyst is added in an amount of 1.5-15 wt. % based on the weight of the thermosetting material.

[0157] In one embodiment, the solvent comprises an aprotic solvent or an ionic liquid. The aprotic solvent comprises dimethylformamide (DMF), dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO) or N-methyl-2-pyrrolidone (NMP). The ionic liquid is a pyridinium cationic ionic liquid or an imidazolium cationic ionic liquid and its corresponding anion is selected from the following groups: BF4-, B(CN)4-, CH3BF3-, CH2CHBF3-, CF3BF3-, C2F5BF3-, n-C3F7BF3-, n-C4F9BF3-, PF6-, CF3CO2-, CF3SO3-, N(SO2CF3)2-, N(COCF3)(SO2CF3)-, N(SO2F)2-, N(CN)2-, C(CN)3-, SCN-, SeCN-, CuCl2-, AlCl4- and F(HF)2.3-.

[0158] In a representative embodiment, waste polycarbonate and diamine are reacted to obtain the (urethane-carbonate) copolymer of the present invention. Waste epoxy resin and the (urethane-carbonate) copolymer are mixed to obtain a recyclable epoxy resin thermosetting composition, which is then heated to obtain a decomposition product, the decomposition product comprising inorganic and organic matter, and the inorganic and organic matter are separated by extraction, crystallization, distillation, filtration or a combination thereof.

[0159] In one embodiment, the inorganic matter is recycled to produce other materials.

[0160] In one embodiment, the organic matter includes an organic compound with a relatively high molecular weight and an organic compound with a relatively low molecular weight.

[0161] In one embodiment, the relatively high molecular weight organic compound is a raw material for recycling epoxy resin, polyurethane, phenolic resin, acrylic resin, polyurethane foam material or reinforced composite material.

[0162] In one embodiment, the relatively low molecular weight organic compound comprises urea, polyurea, cyclic urea, cyclic carbamate monomer or oligomer. The relatively low molecular weight organic compound can be used to manufacture specialty chemicals.

[0163] The following experimental examples are used to illustrate the technical features and effects of the present invention.

[0164] Td5 in the following experimental examples and tables represents the temperature at which the weight loss is 5 wt.% by thermogravimetric analysis (TGA); g It stands for glass transition temperature.

[0165] Experimental Example 1: General Preparation Method of Copolymer [PCC ((Carbamate-Carbonate) Copolymer) Formula (5)]

[0166] First, polycarbonate (PC, 50-100 g) was dissolved in anisole (500 ml) at 75°C, and an amine compound or polyether diamine (10-20 g) was added, stirred and reacted for 3 hours, and the anisole was removed in vacuo to obtain a copolymer (PCC; (carbamate-carbonate) copolymer). FTIR analysis results (cm -1 ,KBr): 3300(-OH), 1775(-C=O(carbonate)) and 1715(-C=O(urethane)). 1H-NMR (600MHz, deuterated dimethyl sulfoxide [d-DMSO]) analysis results: δ (ppm) = δ1.20-1.40, δ1.40-1.50, δ1.50-1.80, δ3.00-3.20, δ3.70-3.90, δ6.60-6.80, δ6.85-7.10, δ7.10-7.40, δ7.60-7.80, δ9.10-9.30. The PCC-number represents the total molar ratio of the m segment in the structure as shown informula (5). For example, PCC-0.5 represents the total molar ratio of the m segment in the structure as shown informula (5) is 0.5. This number is equal to m divided by the sum of m, x and y. According to the preparation method of this experimental example, copolymers PCC-0.25, PCC-0.5 and PCC-0.99 were prepared respectively. 1 The H-NMR spectra are Figure 1 , Figure 2 and Figure 3 shown.

[0167] General steps for a full recycling process of recyclable thermoset components

[0168] The recyclable thermosetting composition with copolymer (PCC) of the present invention can be digested and decomposed with hydroxyl or amino compounds (such as monoamine, diamine or triamine compounds). Specifically, the recyclable thermosetting composition (PCC-BZ, PCC-PF, PMMA / PCC, PCC-Bis-GMA, PCC-Bis-MA, PCC-PU, PCC-PUF or PCC-E, which may contain organic or inorganic fillers) is heated to 100-250°C in the presence of ethanolamine for digestion and decomposition. After 3 hours, the above-mentioned recyclable thermosetting composition is completely dissolved and a decomposition product is obtained. The filler is first separated, and then the phenolic compounds and compounds with carbamate or urea functional groups therein are separated by distillation or extraction procedures, thereby achieving a full recovery effect. Fourier spectroscopy analysis of its decomposition products (cm -1 , KBr): 3300-3400 (-OH of phenol and -COONH), 1716 (-C=O(carbamate) and 1670(-C=O(urea)).

[0169] Experimental Example 2: Preparation of recyclable epoxy resin (PCC-E)

[0170] This experimental example prepares a recyclable epoxy resin (PCC-E) with reference to the composition of Table 1. The thermal properties (thermal decomposition temperature Td and glass transition temperature Tg) of the recyclable epoxy resin are shown in Table 2. Specifically, the epoxy resin (trade name DER332) and the additive / copolymer (PCC) of the present invention are mixed to prepare the recyclable epoxy resin. First, the mixed copolymer [PCC (3.00g)] is in anisole (20ml), and the copolymer is completely dissolved by stirring and heating to 75°C under nitrogen. Then, the epoxy resin [DER332 (6.20g)] dissolved in anisole (4ml) is added, and 2 ml of 0.1wt% triphenylphosphine (TPP)-anisole solution is added. The temperature is raised to 120°C for reaction, and most of the solvent is removed by distillation under reduced pressure. The reaction is continued for 24 hours, and the reaction is monitored by hydrogen nuclear magnetic resonance spectroscopy analysis until the epoxy group stops the ring-opening reaction, which is considered to be the end of the reaction. The Fourier transform infrared spectrum results (cm -1 , KBr): 3300(-OH), 1775(-C=O(carbonate)), 1715(-C=O(urethane)) and 913(oxirane). H NMR spectrum: 1 H-NMR (ppm, DMSO-d6): δ1.20-1.40, δ1.40-1.50, δ1.50-1.70, δ2.65-2.75, δ2.80-2.90, δ2.95-3.15, δ3.25-3.40, δ3.70-3 .90, δ3.90-4.20, δ4.20-4.30, δ6.60-6.70, δ6.80-6.90, δ6.90-7.05, δ7.08-7.20, δ7.20-7.40, δ7.60-7.80, δ9.10-9.30. Usually, the epoxy resin can also be hardened with a crosslinking agent such as polyether polyamine, aliphatic amine, cyclic amine, aromatic amine, polyimide, polyamic acid, dicyandiamide, anhydride, melamine and other hardeners to form a 3D network structure. The catalyst includes Lewis acid, Lewis base, metal alkyl oxide, boron trifluoride complex or free radical initiator. The hardening process can be monitored by Fourier transform infrared spectroscopy analysis. The characteristic peaks of the epoxy group (oxirane functional group at peaks of around 913cm -1 ) disappears.

[0171] Table 1

[0172]

[0173]

[0174] *NPEL-128 is a trade name for a bisphenol A type epoxy resin; DETA is diethylenetriamine.

[0175] Table 2

[0176]

[0177] Experimental Example 2-1: Recycling Procedure of Recyclable Epoxy Resin

[0178] Please refer to Table 3, the recyclable epoxy resin (PCC-E) is mixed with a decomposition agent and a solvent (DMF, DMSO or NMP), the decomposition agent includes 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), zinc oxide (ZnO), boron trifluoride (BF3) or triethylenetetramine (TETA); then heated to 70-220°C to obtain the decomposition product of the recyclable epoxy resin. Please refer to Table 8, the decomposition product of the recyclable epoxy resin is mixed with the listed compounds, and then heated and hardened to obtain a new recycled epoxy resin. The Fourier infrared spectrum of the new recycled epoxy resin is consistent with the characteristic peak of the infrared spectrum of the original recyclable epoxy resin. Based on this, it is confirmed that the recyclable epoxy resin (PCC-E) of the present invention has the technical effect of being fully recyclable and recyclable.

[0179] Table 3

[0180]

[0181] Table 4

[0182]

[0183]

[0184] *NPEL-128 is a trade name for a bisphenol A type epoxy resin.

[0185] Experimental Example 3: Preparation of recyclable polyurethane (PCC-PU) and recyclable polyurethane foam (PCC-PUF)

[0186] In this experimental example, recyclable polyurethane (PCC-PU) and recyclable polyurethane foam material (PCC-PUF) were prepared with reference to the composition of Table 5. The thermal properties and mechanical properties of the recyclable polyurethane (PCC-PU) are shown in Table 6. Generally speaking, a solvent (such as DMF), a diisocyanate (such as MDI) and a polyol (such as PTMEG) are mixed and heated to 60°C under nitrogen to prepare a prepolymer. Two hours later, the copolymer (PCC) of the present invention is added, which takes about 1 hour. A crosslinking agent (TMP) and a catalyst (DBTDL (2 mol% of MDI)) are added to obtain a recyclable polyurethane (PCC-PU) having a crosslinked structure after reaction. On the other hand, the recyclable polyurethane foam material (PCC-PUF) is prepared by the following steps. First, the polyol and the copolymer (PCC) are stirred and mixed at 55°C, silicone oil, water and an amine compound are added, and stirring is continued. Then, an isocyanate (such as HDI) and a catalyst (such as dibutyltin dilaurate, continue to react in a 55°C oven for more than 1 hour and then return to room temperature for 24 hours to obtain a recyclable polyurethane foam material (PCC-PUF). Fourier transform infrared spectroscopy analysis results (FTIR (cm -1 ,KBr)):3300-3400(-COONH) and 1715(-C=O(urethane)).

[0187] Table 5

[0188]

[0189]

[0190] *PLACELL 410 is a trade name for a polyester polyol **T9 is a trade name for a tin compound catalyst

[0191] Table 6

[0192]

[0193]

[0194] Experimental Example 3-1: Recycling Procedure of Recyclable Polyurethane

[0195] Please refer to Table 7, the recyclable polyurethane (PCC-PU) is mixed with a decomposition agent and a solvent (DMF, DMSO or NMP), the decomposition agent includes 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), zinc oxide (ZnO), boron trifluoride (BF3) or triethylenetetramine (TETA); then heated to 70-220°C to obtain the decomposition product of the recyclable polyurethane. Please refer to Table 8, the recyclable polyurethane decomposition product is mixed with the listed compounds, and then heated and hardened to obtain a new recycled polyurethane. The Fourier infrared spectrum of the new recycled polyurethane is consistent with the characteristic peaks of the infrared spectrum of the original recyclable polyurethane, which proves that the recyclable polyurethane of the present invention has the technical effect of being fully recyclable and recyclable.

[0196] Table 7

[0197]

[0198] Table 8

[0199]

[0200]

[0201] *PLACELL 410 is a trade name for a polyester polyol

[0202] Experimental Example 4: Preparation of recyclable acrylic resin (PCC-PMMA)

[0203] The method of Experimental Example 4 is applicable to the preparation of recyclable acrylic resin (PCC-PMMA), recyclable bisphenol A glycidyl methacrylate (PCC-Bis-GMA), recyclable bisphenol acrylic resin (PCC-Bis-MA) and acrylic resin with other modified functional groups. Please refer to the composition shown in Table 9. In one experiment, the MMA monomer and the copolymer (PCC) were first dissolved in THF (50 / 50 by weight), then dried at 60°C to form a film for 1 day, and then treated under vacuum at 125°C for 1 day. The film was cut and then hot-pressed at 200°C for 1 day to obtain a recyclable acrylic resin (PCC-PMMA). In another experiment, the copolymer [PCC (5mmol)], glycidyl methacrylate (glycidyl methacrylate (GMA)) (10mmol) and a tertiary amine (N,N-dimethylbenzylamine (0.05mmol)) were mixed. Heated to 70℃ under argon, maintained for 6 hours, and finally obtained viscous and recyclable bisphenol A glycidyl methacrylate. In another experiment, copolymer [PCC (1.18mmol)], methacrylic anhydride (methacrylic anhydride (1.88mmol)), catalyst [4-(dimethylamino)pyridine (DMAP) (0.01mmol)] and solvent (N,N-dimethylacetamide (DMAc) 10ml) were mixed and stirred at room temperature under nitrogen for 24 hours. Then added to methanol for precipitation, the precipitate was filtered and dried at 80℃, and finally obtained recyclable bisphenol acrylic resin. The above experimental examples all use free radical initiators, which include organometallic compounds and organometallic halides, such as triethylaluminum and titanium tetrachloride, azo compounds (2,2'-azobis (isobutyronitrile) (AIBN)), organic or inorganic peroxide compounds (benzoyl peroxide, di-t-Butyl peroxide) or adding acids, alcohols, amines or thiols. The above reaction uses Fourier transform infrared spectroscopy to monitor the acrylic functional group. The specific Fourier transform infrared spectroscopy results FTIR (cm -1 ,KBr): 3300-3400(-COONH), 1715(-C=O(urethane) and 1600-1680(-C=C(acrylic)).

[0204] Table 9

[0205]

[0206]

[0207] Experimental Example 4-1: Recycling Procedure of Recyclable Acrylic Resin

[0208] Please refer to Table 10, the recyclable acrylic resin (PCC-PMMA) is mixed with a decomposition agent and a solvent (DMF, DMSO or NMP), the decomposition agent includes 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), zinc oxide (ZnO), boron trifluoride (BF3) or triethylenetetramine (TETA); then heated to 70-220°C to obtain the decomposition product of the recyclable acrylic resin. Please refer to Table 11, the decomposition product of the recyclable acrylic resin is mixed with the listed copolymers, and then heated and hardened to obtain a new recycled acrylic resin. The Fourier infrared spectrum of the new recycled acrylic resin is consistent with the characteristic peaks of the infrared spectrum of the original recyclable acrylic resin. Based on this, it is confirmed that the recyclable acrylic resin of the present invention has the technical effect of being fully recyclable and recyclable.

[0209] Table 10

[0210]

[0211] Table 11

[0212]

[0213]

[0214] Experimental Example 5: Preparation of recyclable phenolic resin (PCC-PF)

[0215] This experimental example prepares a recyclable phenolic resin (PCC-PF) with reference to the composition of Table 12. The recyclable phenolic resin can be prepared by reacting a mixture of different copolymers (PCC) and phenol with formaldehyde in the presence of an alkaline catalyst. Specifically, the weight percentage of phenol and copolymer (PCC-0.5) can reach 40wt.%. Among them, phenol (88wt.% aqueous solution), copolymer (PCC) and formaldehyde are mixed and reacted uniformly. At the beginning, the molar ratio of phenol to formaldehyde is 1:1.25; then it is increased to 1:1.50, and finally increased to 1:2.0. Sodium hydroxide aqueous solution [46% (4%, w / w, on basis of total Phenol)] is added, and then reacted at 60°C for 1 hour, heated to 80°C for 1 hour, and then cooled back to 60°C for 1 hour. The resin shown in Table 12 is hardened under an acidic catalyst. The selected acidic catalyst includes xylene sulfonic acid or phosphoric acid aqueous solution. The catalyst addition amount is usually 3-4wt.%. Finally, the curing process was carried out at room temperature for 8 hours, and then matured at 80℃ for another 4 hours to obtain the recyclable phenolic resin (PCC-PF). Fourier transform infrared spectroscopy analysis FTIR (cm -1 ,KBr):3300-3400(-COONH),1715(-C=O(urethane)and 1470(methylene of PF resins).

[0216] Table 12

[0217]

[0218]

[0219] *KB-3640N is a phenolic resin trade name

[0220] **KB-3570H is a phenolic resin trade name

[0221] Experimental Example 5-1: Recycling Procedure of Recyclable Phenolic Resin

[0222] Please refer to Table 13, the recyclable phenolic resin (PCC-PF) is mixed with a decomposition agent and a solvent (DMF, DMSO or NMP), the decomposition agent includes 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), zinc oxide (ZnO), boron trifluoride (BF3) or triethylenetetramine (TETA); then heated to 70-220°C to obtain the decomposition product of the recyclable phenolic resin. Please refer to Table 14, the decomposition product of the recyclable phenolic resin is mixed with the listed resins, and then heated and hardened to obtain a new recycled phenolic resin. The Fourier infrared spectrum of the new recycled phenolic resin is consistent with the characteristic peaks of the infrared spectrum of the original recyclable phenolic resin. Based on this, it is confirmed that the recyclable phenolic resin of the present invention has the technical effect of being fully recyclable and recyclable.

[0223] Table 13

[0224]

[0225] Table 14

[0226]

[0227] Experimental Example 6: Preparation of recyclable composite material (PCC-C)

[0228] This experimental example prepares a recyclable composite material (PCC-C) with reference to the composition of Table 15. Specifically, the copolymer (PCC) of the present invention is dissolved in anisole (50ml) at 75°C and nitrogen, and then APTES (20mmol) is added and stirred for 3 hours. After vacuum distillation to remove anisole, a siliconized copolymer (PCC-1.0S) is obtained. Diisocyanates (such as MDI or IPDI) and / or polyols can prepare polyurethanes (silane-containing PU) with silane groups. Therefore, a mixture of diisocyanates, polyols and copolymers (PCC-1.0S) is dissolved in DMF for polymerization, wherein the equivalent ratio of NCO / OH is 1:1. The polymerization reaction is carried out at 80°C and nitrogen for 3 hours. Then a solution of a compound with a silane group and TEOS (or nanosilicon spheres) is added, and DMF is added to dilute to a solid content of 10wt.%, and a drop of concentrated hydrochloric acid (HCl, 12M) and a small amount of deionized water are added to obtain a mixture of a homogeneous phase. The homogeneous mixture was poured into a Teflon container and placed in a 60°C oven, heated to 100°C at a heating rate (10°C / h) and maintained for 6 hours to obtain a recyclable PU / SiO2 composite material. Fourier transform infrared spectroscopy analysis of the original PC polymer, 1773cm -1 The characteristic peak representing the carbonate group disappeared after digestion, and the peak at 1716 cm -1The characteristic peaks representing the urethane group are generated. In addition, 956cm -1 The characteristic peaks represent the formation of siloxane (-Si-OR) groups. The above results indicate that the PC polymer has been successfully converted and introduced with other functional groups (ie, phenolic carbamate, silane and hydroxyl groups). The structure was analyzed using Fourier transform infrared spectroscopy, 1721cm -1 Indicates the formation of carbamate, 953cm -1 Indicates the formation of siloxane (-Si-OR) groups, 1015-1050 and 800cm -1 In other words, the recyclable composite material of the present invention is prepared by a sol-gel process. FTIR analysis (cm -1 ,KBr):3300-3400(-COONH),1716(-C=O(urethane),1015-1050,956(Si-OR)and800cm -1 [-Si-O-Si-,silica group]).

[0229] Table 15

[0230]

[0231] Experimental Example 6-1: Recycling Process of Recyclable Composite Materials

[0232] Please refer to Table 16, the recyclable composite material (PCC-C) is mixed with a decomposition agent and a solvent (DMF, DMSO or NMP), the decomposition agent includes 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), zinc oxide (ZnO), boron trifluoride (BF3) or triethylenetetramine (TETA); then heated to 70-220°C to obtain the decomposition product of the recyclable composite material. Please refer to Table 17, the decomposition product of the recyclable composite material is mixed with isocyanate, and then heated and hardened to obtain a new recycled composite material, the Fourier infrared spectrum of the new recycled composite material and the characteristic peak of the infrared spectrum of the original recyclable composite material are consistent, thereby confirming that the recyclable composite material of the present invention has the technical effect of being fully recyclable and recyclable.

[0233] Table 16

[0234]

[0235]

[0236] Table 17

[0237]

[0238] Experimental Example 7: Preparation of recyclable benzoxazine resin (PCC-BZ)

[0239] In this experimental example, various recyclable benzoxazine resins (PCC-BZ) were prepared with reference to the composition of Table 18. Specifically, the composition listed in Table 18 was added to isopropanol, heated and refluxed for three days until the reaction was complete, and then the isopropanol was removed. The obtained colloidal product was dissolved in chloroform and washed with 1N sodium hydroxide aqueous solution three times. Finally, it was dried over anhydrous magnesium sulfate. Fourier transform infrared spectroscopy analysis of the product showed that the product had a peak value of 1.244 nm at 1215 cm -1 ,1030cm -1 and 960cm -1 The product has an absorption peak, indicating that the product has a typical benzoxazine structure. After the product is hardened, a recyclable benzoxazine resin is obtained. Fourier transform infrared spectroscopy analysis (FTIR (KBr)): 3300-3400m -1 (-COONH),1715cm -1 (-C=O(urethane),1215cm -1 (asymmetric stretching COC),1030cm -1 (symmetric stretching of COC),930-960cm -1 (benzoxazine).

[0240] Table 18

[0241]

[0242]

[0243] MDI: Methylene diphenyl diisocyanate

[0244] PTMEG2000: Polytetramethylene ether glycol

[0245] PCDL2000: Polycarbonate diol

[0246] Experimental Example 7-1: Recycling Procedure of Recyclable Benzoxazine Resin

[0247] Please refer to Table 19, the recyclable benzoxazine (BZ) resin (PCC-BZ) is mixed with a decomposition agent and a solvent (DMF, DMSO or NMP), and the decomposition agent includes 1,8-diazabicyclo [5.4.0] undec-7-ene (DBU), zinc oxide (ZnO), boron trifluoride (BF3) or triethylenetetramine (TETA); then heated to 70-220°C to obtain the recyclable benzoxazine (BZ) resin decomposition product. Please refer to Table 20, the benzoxazine (BZ) resin decomposition product is mixed with the reagents listed in Table 20, and then heated and hardened to obtain a new recycled benzoxazine (BZ) resin. The Fourier infrared spectrum of the new recycled benzoxazine (BZ) resin is consistent with the characteristic peak of the infrared spectrum of the original recyclable benzoxazine (BZ) resin. Based on this, it is confirmed that the recyclable benzoxazine (BZ) resin of the present invention has the technical effect of being fully recyclable and recyclable.

[0248] Table 19

[0249]

[0250] Table 20

[0251]

[0252] Experimental Example 8: Preparation of an aqueous dispersion of a recyclable thermosetting resin (PCC-BZ, PCC-PF, PCC-PMMA, PCC-Bis-GMA, PCC-Bis-MA, PCC-PU, PCC-PUF or PCC-E)

[0253] First, a recyclable thermosetting resin (such as PCC-BZ, PCC-PF, PCC-PMMA, PCC-Bis-GMA, PCC-Bis-MA, PCC-PU, PCC-PUF or PCC-E) containing the copolymer (PCC) of the present invention is dissolved in a polar solvent (MEK or THF), an emulsifier (such as Jeffamine M2070, M1000 or ED2003) is added, and then stirred (2000-rpm) for 1 hour; wherein the weight ratio of the copolymer (PCC), the emulsifier and the solvent (MEK) is 20:3:17. Then, deionized water is added at a rate (1 g / min), and the addition is stopped when the weight ratio of water to oil (non-aqueous medium) exceeds 0.5, thereby forming an aqueous dispersion containing a recyclable thermosetting resin. A reduced pressure distillation is performed to make the solid content of the aqueous dispersion of the recyclable thermosetting resin reach 5 to 70 wt%. After hardening or coating and drying, the corresponding recyclable thermosetting resin structure can be obtained. The characteristic peaks of the corresponding structure can be obtained by Fourier transform infrared spectroscopy analysis. FTIR (cm -1 ,KBr):3300-3400cm-1 (-COONH); 1715cm -1 (-C=O(urethane); 1215cm -1 (asymmetric stretching of COC); 1030cm -1 (symmetric stretching of COC),930-960cm -1 (benzoxazine); 1015-1050cm -1 ; 956(Si-OR); 800cm -1 [-Si-O-Si-,silica group]); 1470cm -1 (methylene of PF resins);1600-1680cm -1 (-C=C(acrylic));1600-1680cm -1 (-C=C(acrylic)); 913cm -1 (oxirane).

[0254] The above are only preferred embodiments of the present application, and are not intended to limit the present application in any form. Although the present application has been disclosed as a preferred embodiment as above, it is not intended to limit the present application. Any technician familiar with the profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present application. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. An additive for recycling thermosetting materials, the composition of which comprises a copolymer having at least one urethane group, at least one carbonate group and / or at least one urea group, and the number average molecular weight of the copolymer is in the range of 100-50,000 Da.

2. The additive for recycling thermosetting materials according to claim 1, wherein the copolymer is a (urethane-carbonate) copolymer, a (urethane-urea) copolymer, a (carbonate-urea) copolymer, a (urethane-carbonate-urea) copolymer or a combination thereof.

3. The additive for recycling thermosetting materials according to claim 1, wherein the urethane group has a structure of formula (1) or formula (2); in, R1 is a linear or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a polyether group having a molecular weight of 50 to 10,000, or a polysiloxane group having a molecular weight of 50 to 10,000; R2 is a straight chain or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a phenyl group, an alkylphenyl group having 7 to 20 carbon atoms, or an alkylphenol group having 6 to 20 carbon atoms; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group or an amide group; X is a linear or branched alkyl group having 2-20 carbon atoms, a cyclic alkyl group having 3-8 carbon atoms, a polyether group having a molecular weight of 50-10,000, or a polysiloxane group having a molecular weight of 50-10,000, and n is an integer of 1-10.

4. The additive for recycling thermosetting materials according to claim 1, wherein the carbonate group has a structure as shown in formula (3); in, R2 is a straight chain or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a phenyl group, an alkylphenyl group having 7 to 20 carbon atoms, or an alkylphenol group having 6 to 20 carbon atoms.

5. The additive for recycling thermosetting materials according to claim 1, wherein the urea group has a structure as shown in formula (4); in, R1 is a linear or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a polyether group having a molecular weight of 50 to 10,000, or a polysiloxane group having a molecular weight of 50 to 10,000; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group or an amide group; X is a linear or branched alkyl group having 2-20 carbon atoms, a cyclic alkyl group having 3-8 carbon atoms, a polyether group having a molecular weight of 50-10,000, or a polysiloxane group having a molecular weight of 50-10,000, and n is an integer of 1-10.

6. A recyclable thermosetting composition comprising a copolymer and a thermosetting material, wherein the copolymer has at least one carbamate group, at least one carbonate group and / or at least one urea group, and the weight percentage of the copolymer is 0.1-85wt.% based on the total weight of the recyclable thermosetting composition.

7. The recyclable thermosetting composition of claim 6, wherein the copolymer is a (urethane-carbonate) copolymer, a (urethane-urea) copolymer, a (carbonate-urea) copolymer, a (urethane-carbonate-urea) copolymer, or a combination thereof.

8. The recyclable thermosetting composition according to claim 6, wherein the number average molecular weight of the copolymer is in the range of 100-50,000 Da.

9. The recyclable thermosetting composition according to claim 6, wherein the thermosetting material comprises polyurethane, polyurethane foam, epoxy resin, phenolic resin, reinforced composite material, benzoxazine resin, acrylic resin or a combination thereof.

10. The recyclable thermosetting composition according to claim 6, wherein the urethane group has a structure of formula (1) or formula (2); in, R1 is a linear or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a polyether group having a molecular weight of 50 to 10,000, or a polysiloxane group having a molecular weight of 50 to 10,000; R2 is a straight chain or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a phenyl group, an alkylphenyl group having 7 to 20 carbon atoms, or an alkylphenol group having 6 to 20 carbon atoms; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group or an amide group; X is a linear or branched alkyl group having 2-20 carbon atoms, a cyclic alkyl group having 3-8 carbon atoms, a polyether group having a molecular weight of 50-10,000, or a polysiloxane group having a molecular weight of 50-10,000, and n is an integer of 1-10.

11. The recyclable thermosetting composition according to claim 6, wherein the carbonate group has a structure as shown in formula (3); in, R2 is a straight chain or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a phenyl group, an alkylphenyl group having 7 to 20 carbon atoms, or an alkylphenol group having 6 to 20 carbon atoms.

12. The recyclable thermosetting composition according to claim 6, wherein the urea group has a structure as shown in formula (4); in, R1 is a linear or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a polyether group having a molecular weight of 50 to 10,000, or a polysiloxane group having a molecular weight of 50 to 10,000; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group or an amide group; X is a linear or branched alkyl group having 2-20 carbon atoms, a cyclic alkyl group having 3-8 carbon atoms, a polyether group having a molecular weight of 50-10,000, or a polysiloxane group having a molecular weight of 50-10,000, and n is an integer of 1-10.

13. A process for recycling waste thermosetting materials, comprising: Providing a mixture comprising at least one copolymer, at least one processing aid and at least one waste thermosetting material, the copolymer having at least one urethane group, at least one carbonate group and / or at least one urea group, and the weight percentage of the copolymer is 0.1-85 wt.% based on the total weight of the mixture; Heating the mixture to 50-220° C., thereby obtaining a product, the product comprising inorganic and organic matter; Performing a first process to separate the inorganic and organic substances, the first process comprising extraction, crystallization, distillation, filtration or a combination thereof; the organic substances comprising organic compounds with higher molecular weight and organic compounds with lower molecular weight; and A second process is performed to separate the organic compound with a higher molecular weight from the organic compound with a lower molecular weight, wherein the second process comprises extraction, crystallization, distillation, filtration or a combination thereof.

14. The process for recycling waste thermosetting materials according to claim 13, wherein the copolymer is a (urethane carbonate) copolymer, a (urethane-urea) copolymer, a (carbonate-urea) copolymer, a (urethane-carbonate-urea) copolymer or a combination thereof.

15. The process for recycling waste thermosetting materials according to claim 13, wherein the number average molecular weight of the copolymer is in the range of 100-50,000 Da.

16. The process for recycling waste thermosetting materials according to claim 13, wherein the thermosetting material comprises polyurethane, polyurethane foam material, epoxy resin, phenolic resin, reinforced composite material, benzoxazine resin, acrylic resin or a combination thereof.

17. The process for recycling waste thermosetting materials according to claim 13, wherein the carbamate group has a structure of formula (1) or formula (2); in, R1 is a linear or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a polyether group having a molecular weight of 50 to 10,000, or a polysiloxane group having a molecular weight of 50 to 10,000; R2 is a straight chain or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a phenyl group, an alkylphenyl group having 7 to 20 carbon atoms, or an alkylphenol group having 6 to 20 carbon atoms; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group or an amide group; X is a linear or branched alkyl group having 2-20 carbon atoms, a cyclic alkyl group having 3-8 carbon atoms, a polyether group having a molecular weight of 50-10,000, or a polysiloxane group having a molecular weight of 50-10,000, and n is an integer of 1-10.

18. The process for recycling waste thermosetting materials according to claim 13, wherein the carbonate-based The group has a structure as shown in formula (3); in, R2 is a straight chain or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a phenyl group, an alkylphenyl group having 7 to 20 carbon atoms, or an alkylphenol group having 6 to 20 carbon atoms.

19. The process for recycling waste thermosetting materials according to claim 13, wherein the urea group has a structure as shown in formula (4); in, R1 is a linear or branched alkyl group having 2 to 20 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a polyether group having a molecular weight of 50 to 10,000, or a polysiloxane group having a molecular weight of 50 to 10,000; R3 is a hydroxyl group, an amine group, a carbonyl group, a carboxylic acid group, an ester group or an amide group; X is a linear or branched alkyl group having 2-20 carbon atoms, a cyclic alkyl group having 3-8 carbon atoms, a polyether group having a molecular weight of 50-10,000, or a polysiloxane group having a molecular weight of 50-10,000, and n is an integer of 1-10.